Fluid and thermal effect on temperature-dependent power increase of electric vehicle's permanent magnet synchronous motor using compound water cooling method - Zichao Zhang; Qiang Song; Bilal Ahmed; Yuecheng Han (Case Studies in Thermal Engineering)
Taking advantage of compound housing water jacket (HWJ) and hollow-shaft water jacket (SWJ) cooling based on the temperature-dependent power of permanent magnet synchronous motor (PMSM) is a solution for enhanced electric vehicle (EV) performance. The fluid and temperature field of a 40 kW PMSM at three typical continuous working points were studied, covering low to high speeds of EVs. The influence of different coolant flowrates on power of motor was obtained by multi-physics field coupling analysis method. The impact of current control modes was also investigated. 3D computational fluid dynamics (CFD) conjugate heat transfer calculation combined with 3D lumped parameter thermal network (LPTN) was adopted to calculate the flow and temperature. Temperature-dependent material properties were taken into consideration in electromagnetic finite element analysis (FEA). The models were modified and validated by experiments. Once compounding SWJ on the basis of a strong HWJ cooling, the PM temperature can continue to decrease over 20 degC. The insensitive characteristic of PM temperature towards SWJ flow rate was observed. Under constant current control mode, 3.8 %, 6 % and 4 % PMSM power enhancement by compound cooling were proved at three typical working points. Under current open-loop, 7 %, 16 %, and 10 % increases with compound cooling were confirmed.